Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1051/0004-6361/201629724
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectroscopy, tentative interstellar detection, and chemical modeling of N-methylformamide

Abstract: Context. N-methylformamide, CH 3 NHCHO, may be an important molecule for interstellar pre-biotic chemistry because it contains a peptide bond, which in terrestrial chemistry is responsible for linking amino acids in proteins. The rotational spectrum of the most stable trans conformer of N-methylformamide is complicated by strong torsion-rotation interaction due to the low barrier of the methyl torsion. For this reason, the theoretical description of the rotational spectrum of the trans conformer has up to now … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
261
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(275 citation statements)
references
References 48 publications
8
261
2
Order By: Relevance
“…We used this model to search for urea toward N2. No sign of urea was found and the upper limit on its column density is reported in Table 6, assuming the same rotational temperature (180 K) and source size (0.9 ′′ ) as derived for CH 3 C(O)NH 2 toward N2 by Belloche et al (2017). The upper limit lies more than one order of magnitude below the column density derived for urea toward N1S.…”
Section: Moleculementioning
confidence: 69%
“…We used this model to search for urea toward N2. No sign of urea was found and the upper limit on its column density is reported in Table 6, assuming the same rotational temperature (180 K) and source size (0.9 ′′ ) as derived for CH 3 C(O)NH 2 toward N2 by Belloche et al (2017). The upper limit lies more than one order of magnitude below the column density derived for urea toward N1S.…”
Section: Moleculementioning
confidence: 69%
“…Modeling by Garrod et al (2008) shows that HNCO formation is efficient only by the gas-phase destruction of more complex grain-surface products, urea in particular. However, the recent model of Belloche et al (2017) suggests reaction between NH and CO may be efficient (see Section 5.2). Several aspects of our HNCO observations support a scenario in which HNCO mainly forms through atom addition ice chemistry in the cold envelope.…”
Section: Com Formation Chemistrymentioning
confidence: 99%
“…The underproduction of HNCO by several orders of magnitude is likely a result of an over-estimated barrier for the grain surface process of NH + CO → HNCO, which impedes efficient grain-surface formation of HNCO in the model. While there are no strong constraints on this barrier from laboratory work, recent modeling work by Belloche et al (2017) tested several values ranging from 1000 -2500K, the latter value being the one used in our present study. They found that the barrier is required to be no greater than ∼1500K in order to produce sufficient HNCO to explain observed abundances of CH 3 NCO.…”
Section: Modeled Vs Observed Chemistrymentioning
confidence: 99%
“…In an initial effort to explore the ability of the model to reproduce the observed abundance, we modified the model with the back-diffusion correction of Willis & Garrod (2017), and used a network based on that of Belloche et al (2017), in which CH 3 OCH 2 OH is produced via Reaction 4. The network also contains likely gas-phase and grain-surface destruction mechanisms for CH 3 OCH 2 OH.…”
Section: Chemical Modelingmentioning
confidence: 99%